Teaching and learning in higher education (TLHE) / Mohd Syafiq Abdul Rahman ... [et al.] - Abdul Rahman, Mohd Syafiq; Libasin, Zuraira; Warris, Saiful Nizam; Mustapa,, Farah Hayati (Unit Penerbitan JSKM, 2020)
Lecture slides are usually a summary of the lecture content. In lectures, note taking supports to concentrate on what the lecturer is saying, and they guide how your note taking and help you recognize the key topics and concepts. Take note of what seems on them, but don’t confine your notetaking to simply copying it. Taking your own notes will encourage a deeper understanding of the content of the lecture. You can also take notes from a written source which will help you in writing an essay. You can include notes showing your own thoughts about a written source or a lecture to determine how you are going to use the information in your essay. The information is usually very limited compared to what the lecturer says, so it’s more effective to listen to the lecture and take notes from that. Most lecturers make their slides accessible before class, so print them out and take additional notes in the lecture. You’ll get most out of lectures if you do both, but don’t focus on getting everything down to the extent that you miss what the lecturer is saying. But remember that actively listening and thinking are what is important. Regarding the encoding function, two aspects of notetaking are probably most relevant: (a) what method students use to take notes and (b) whether students try to organize their notes as they take them. With respect to note-taking methods, students can take notes by longhand in a notebook or using an electronic device (e.g., a tablet or eWriter), or they can type notes on a laptop computer or tablet. In realistic research of which method is best, taking notes longhand has generally produced as good or better performance outcomes when studied in real- life progresses and in the laboratory (Carter, Greenberg, & Walker, 2017; Luo, Kiewra,